Reflections on the US FDA's Warning on Direct-to-Consumer Genetic Testing - Seon-Hee Yim; Yeun-Jun Chung (Genomics & Informatics)
In November 2013, the US Food and Drug Administration (FDA) sent a warning letter to 23andMe, Inc. and ordered the company to discontinue marketing of the 23andMe Personal Genome Service (PGS) until it receives FDA marketing authorization for the device. The FDA considers the PGS as an unclassified medical device, which requires premarket approval or de novo classification. Opponents of the FDA's action expressed their concerns, saying that the FDA is overcautious and paternalistic, which violates consumers' rights and might stifle the consumer genomics field itself, and insisted that the agency should not restrict direct-to-consumer (DTC) genomic testing without empirical evidence of harm. Proponents support the agency's action as protection of consumers from potentially invalid and almost useless information. This action was also significant, since it reflected the FDA's attitude towards medical application of next-generation sequencing techniques. In this review, we followed up on the FDA-23andMe incident and evaluated the problems and prospects for DTC genetic testing.